MINUMAN FUNGSIONAL SERBUK INSTAN KAYA ANTIOKSIDAN DARI BAHAN NABATI - Govinda Anggita Fortin; Khusnul Khotimah Putri Asnia; Amoria Suci Ramadhani; Maherawati Maherawati (AGROINTEK, 2021)
Functional drinks are known as potential products to be developed. Consuming functional drinks regularly can maintain a healthy body. The purpose of this narrative review is to find out various kinds of vegetable ingredients that can be used for instant powder functional drinks that have antioxidants. Antioxidants are molecules that can slow down or prevent the oxidation process of other molecules. The method of compiling this narrative review is literature search through online media. The process of making functional drinks by means of co-crystallization, foam mat drying, freeze drying and direct heating. In conclusion, the highest antioxidant drinks are as much as 40.02% from seaweed extract and as much as 40.25% for dragon fruit extract. Apart from that, their antioxidant activity is also diverse, such as instant powder functional drinks from curcuma and turmeric.